SPATIAL CARRYING CAPACITY IN KUTA TOURISM AREA FOR REVISITING TOURISTS - Astawa, I; Suardani, Anak (PEOPLE: International Journal of Social Sciences, 2017)
Kuta is the pioneer of tourism starts from the early 20th century when Bali was recently discovered as a tourism area. The community relies largely on tourism revenues, yet carrying capacity and revisiting tourists research has not been done. This study therefore, attempts to analyze(1)influence of congestion/density, (2) influence of cleanliness, (3) influence of land and (4) influence of design/layout respectively on revisiting tourists.Data collected through questionnaires and conducted at 80 tourists in Kuta tourism area. Multiple regression analysis used in this study. The analysis showed that congestion/density has a positive and significant effect on revisiting tourists. Cleanliness, land, and design/layout has a positive effect but not significant. The positive impact of socioeconomic are rising incomes, increasing employment, and knowledge for the local community. While the negative impacts such as consumptive lifestyles, the population density, and less land.Further research needs to be done to assess the economic aspects, develop future research projects relating to environmental tourism areas and revisiting tourists’ behaviors.